Can dietary self-reports usefully complement blood concentrations for estimation of micronutrient intake and chronic disease associations?. Issue 1 (4th March 2020) - Prentice, Ross L; Pettinger, Mary; Neuhouser, Marian L; Tinker, Lesley F; Huang, Ying; Zheng, Cheng; Manson, JoAnn E; Mossavar-Rahmani, Yasmin; Anderson, Garnet L; Lampe, Johanna W
ABSTRACT: Background: We recently presented associations between serum-based biomarkers of carotenoid and tocopherol intake and chronic disease risk in a Women's Health Initiative (WHI) Measurement Precision subcohort ( n  = 5488). Questions remain as to whether self-reported dietary data can usefully augment such biomarkers or can be calibrated using biomarkers for reliable disease association estimation in larger WHI cohorts. Objectives: The aims were to examine the potential of FFQ data to explain intake variation in a WHI Feeding Study and to compare association parameter estimates and their precision from studies based on biomarker-calibrated FFQ intake in larger WHI cohorts, with those previously presented. Methods: Serum-based intake measures were augmented by using FFQ data in a WHI Feeding Study ( n  = 153). Corresponding calibration equations were generated, both in a companion Nutritional Biomarker Study ( n  = 436) and in the previously mentioned subcohort ( n  = 5488), by regressing these intake measures on dietary data and participant characteristics, for α- and β-carotene, lutein plus zeaxanthin, and α-tocopherol. The supplemental value of FFQ data was considered by examining the fraction of feeding study intake variation explained by these regression models. Calibrated intake and disease association analyses were evaluated by comparisons with previously reported subcohort results. Results: The inclusion of FFQ data led to some increases in feeding study intake variation explained (total R 2 of ∼50%). Calibrated intake estimates explained 25–75% of serum-based intake variation, whether developed using either of the 2 cohort subsamples. Related disease associations for micronutrients were precisely estimated in larger WHI cohorts ( n  = 76, 691) but were often closer to the null compared with previously reported associations. Conclusions: FFQ data may usefully augment blood concentrations in estimating the intake of carotenoids and tocopherols. Calibrated intake estimates using FFQ, dietary supplement, and participant characteristics only may require further justification to ensure reliable estimation of related disease associations.